Flexible institutional arrangements and labour productivity: the case of transit industry in the United States. Issue 1 (January 2017) - Smirnova, Olga V.
Abstract: Using the US National Transit Database 1994–2006, the manuscript empirically tests the influence of several institutional arrangements on labour productivity. The main finding of the paper is that not all flexible institutional arrangements may translate into labour productivity gains in the mass transit. While partial contracting may increase labour productivity in the US transit sector during the study period, the special governance actually decreases labour productivity. The potential implications for improvements in labour productivity are discussed.